COVID-19 IMPLICATION AS RISK FACTOR FOR STROKE - Dolnenec-Baneva, Natalija; Taravari, Arben; Petrovska-Cvetkovska, Dragana; Medjiti, Fatmir; Mitrevska-Velkov, Jasmina; Baneva, Evgenija (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
COVID-19 has become a global pandemic, affecting millions of people. This aerosol infection caused by SARS-CoV-2 possess a wide  range of symptoms, varying from being asymptomatic to fatal, from simple (cold, cough and flu) to severe pneumonia and respiratory distress.  But COVID-19 can affect other organs, including the brain (central and peripheral nervous system). COVID-19 patients presented a wide range of  neurological symptoms (headache, dizziness, anosmia, ageusia, confusion) and neurological disorders (encephalitis, encephalopathies,  myelitis, cranial nerves damage, Gullian-Barre polyradiculoneuritis and its variants, neuropathies, myopathy, seizures, neurodegenerative diseases), among  which stroke is the most prevalent and devastating, presented as an independent risk factor for poor prognosis. Several studies of acute stroke in COVID-19 patients, reported  both acute ischemic stroke and acute cerebral hemorrhage (up 6% of  individuals with COVID-19 suffered acute stroke). The stroke risk was highest in those most severely infected and those with pre-existing vascular risk factors. Most strokes were ischemic and there was an increase in large vessel occlusion, suggesting that cerebral thrombosis and/or thromboembolism could be possible causative pathways for the disease. The relationship between COVID-19 and acute stroke is unclear. The pattern of stroke differs from that in a non-COVID-19 stroke population. The understanding of the underlying mechanism between COVID-19 and stroke warrants further study, so does the development of an effective therapeutic or preventive intervention. Keywords : COVID-19, SARS-CoV-2, stroke, ischemic stroke, hemorrhagic stroke. https://doi.org/10.55302/JMS2143176db